A Design and Build a Marketing System UMKM Sumatera Utara With the OOAD Method Approach - Rina Anugrahwaty; Ajulio Padly Sembiring; Sharfina Faza; Wiwin Sry Adinda Banjarnahor (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
Based on the results of the analysis and design that has been carried out regarding the study of electronic-based North Sumatra KUMKM community development analysis (E-Community KUMKM North Sumatra), a conclusion can be drawn as follows, namely the results of the design using the Object Oriented Analysis Design (OOAD) method, all interfaces are designed very interactive so as to facilitate implementation in the system. Using UML as a visualization medium for system design can make the designed model closer to reality. So as to facilitate the development of the system and its application. Based on the results of the analysis using the Performance, information, economic, control, efficiency, service (PIECES) method, the limitations in marketing the results of North Sumatra KUMKM can be solved using information technology, namely the web-based KUMKM E-Community system.